2020
DOI: 10.1016/j.jclepro.2020.121618
|View full text |Cite
|
Sign up to set email alerts
|

Influence of period light on cultivation of microalgae consortium for the treatment of tannery wastewaters from leather finishing stage

Abstract: Wastewater from the leather finishing step in tanneries contains high nutrient loads and toxic compounds, such as dyes, acids, toxic metals among others. To our best knowledge, for the first time, the influence of light period on the treatment of wet-end and finishing leather wastewaters with a microalgae consortium containing mainly Tetraselmis sp. was investigated. In this work, a microalgae consortium present the ability to grow well in this kind of tannery wastewater and was used for reducing nitrogen, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…To the best of the author's knowledge, the literature on the utilization of tannery wastewater using microalgae is scarce. The use of microalgae consortia using tannery wastewater effluents after primary treatment has been reported [30]; similarly, the effect of light on the removal efficiency of Scenedesmus sp. has been reported for this type of wastewater [25].…”
Section: Introductionmentioning
confidence: 94%
“…To the best of the author's knowledge, the literature on the utilization of tannery wastewater using microalgae is scarce. The use of microalgae consortia using tannery wastewater effluents after primary treatment has been reported [30]; similarly, the effect of light on the removal efficiency of Scenedesmus sp. has been reported for this type of wastewater [25].…”
Section: Introductionmentioning
confidence: 94%
“…Different Tetraselmis strains have been reported for the treatment of several industrial wastewaters. For example, leather process industries generate tannery wastewater that contains a high nutrient load, Pena et al (2020) reported that Tetraselmis sp. in consortia with other microalgae showed maximum removal efficiency for tannery wastewater.…”
Section: Industrial Wastewatermentioning
confidence: 99%
“…with other microalgae can increase the nutrient removal efficiency. For example, Pena et al (2020) studied the effect of consortia of microalgae especially Tetraselmis sp. to treat the tannery wastewater.…”
Section: Co-cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Salts are not efficiently removed in conventional treatment (de la Luz-Pedro et al 2019; Kozik et al 2019;Pena et al 2020;Hansen et al 2021c). Furthermore, salts may cause problems for the reuse of effluents in the post-tanning process.…”
Section: Characterization Of Residual Bathsmentioning
confidence: 99%